Seroprevalence of canine brucellosis in the district of Los Olivos, Lima, Peru - Maza V., María (2016)
The study evaluated the seroprevalence of canine brucelosis in the district of Los Olivos, Lima, Peru by the Agar Gel Immunodifussion test (AGID). Blood samples (n=288) were collected from dogs older than 2 months of age. The sera were tested for Brucella canis. The seroprevalence of canine brucelosis was 4.9 ± 1.8% (95% CI) and the corrected seroprevalence was 5.3 ± 2.6% (95% CI), without significant association for age, sex, physical condition, indoor/outdoor habits and reproductive history.